Role of suspended particulate material on growth and metal bioaccumulation in oysters (Crassostrea gigas) from a French coastal semi-enclosed production area, Arcachon Bay - Chouvelon, Tiphaine; Auby, Isabelle; Mornet, Line; Bruzac, Sandrine; Charlier, Karine; Araújo, Daniel Ferreira; Gonzalez, Jean-Louis; Gonzalez, Patrice; Gourves, Pierre-Yves; Méteigner, Claire; Perrière-Rumèbe, Myriam; Rigouin, Loïc; et al. (Journal of marine systems, 2022)
Arcachon Bay is a prominent oyster production area on the coast of Western Europe, and is subject to chemical contamination including by trace metals. Recently, the national “mussel-watch” monitoring network – using local bivalves as semi-quantitative bioindicators of coastal chemical contamination – highlighted a significant increase in copper (Cu) concentrations in oysters from this bay. Here, we conducted a one-year multi-compartment and multi-parameter field study to investigate some aspects of the surrounding environment of oysters that could explain their metal bioaccumulation. Sediment, seawater (through punctual and passive sampling), particles (suspended particulate material of selected sizes, including trophic resources for oysters) and transplanted oysters were regularly collected at two contrasted sites of the bay (i.e. under continental versus more oceanic influence). These matrices were characterised for their total Cu, zinc (Zn), nickel (Ni), cadmium (Cd) and lead (Pb) concentrations. Several physico-chemical and biological parameters (e.g. salinity, particle loads, oyster growth rate and condition indices, carbon and nitrogen stable isotope compositions, etc.) were also analysed. Overall, sediment, particles and oysters from the outermost site had slightly lower δ13C values, confirming the more oceanic influence in this part of the bay. Among organic particles, although dinoflagellates tended to be more abundant at the outermost site while ciliates were more abundant at the innermost site of the bay, the two sites did not differ in mean total microphytoplankton and diatom densities. However, the variations observed for most of the other parameters studied show that oysters located near the continental shore are exposed to higher loads of particles in general, and to higher metal contents in the dissolved phase and “bulk” seawater (dissolved plus particulate phases) during the year. While fluvial inputs and continental/urban run-offs are suspected sources of anthropogenic metal inputs into the bay, (fine) sediment particle resuspension appears to be a likely major contributor to metal release and hence to the contamination of the bay including oysters. The decline of seagrass beds in the last two decades in the bay could also have decreased the potential of fine particle retention in the sedimentary stratum. Concomitantly, oysters presenting the highest metal concentrations were those with the lower growth rates and condition indices, which may be induced by physical constraints, high amounts of pseudo-faeces produced and/or reduced food and energy acquisition by oysters due to high particle loads in the water column. The findings of this study imply that using raw metal concentrations in bivalves to monitor marine coastal contamination can lead to misleading interpretations if potentially great spatial variations in bivalve growth rates or condition indices are not considered. Finally, peculiar trends were observed for Cu compared to other metals, highlighting the need of further studies to fully address the Cu contamination in this marine system (e.g. specific sources of contamination for this metal in the bay). This study more broadly raises the issue of potentially man-induced ecological changes (e.g. modification of natural habitats) and their consequences on metal transfer and physiological performance of marine biota. •A multi-compartment and multi-parameter study to unravel oyster metal contamination.•Higher contamination found in dissolved and particulate seawater phases inside the bay.•Contamination likely explained by river flows and tidal resuspension of sediments.•Higher particle loads observed with higher oyster metal concentrations and lower growth.•Differences in oyster bioaccumulation patterns for copper compared to other metals.